Klaas van Gelder, Regime Change at a Distance. Austria and the Southern Netherlands Following the War of the Spanish Succession (1716-1725) - Duerloo, Luc (BMGN - Low Countries Historical Review, 2017)
Klaas van Gelder, Regime Change at a Distance. Austria and the Southern Netherlands Following the War of the Spanish Succession (1716-1725) (Dissertation Ghent University 2012; Verhandelingen van de Koninklijke Vlaamse Academie van België voor Wetenschappen en Kunsten, Nieuwe reeks 29; Leuven/Parijs/Bristol: Peeters, 2016, 449 pp., ISBN 978 90 4293 242 5).